Korea’s ODA Policy Direction for Azerbaijan: Strengthening Azerbaijan’s Innovation Policy Capabilities (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The primary aim of this study is to identify the policy issues that are important in terms of the national development of Azerbaijan, an exercise which has not been undertaken either at home or abroad. The secondary purpose is to study how addressing these policy issues can be supported in Azerbaijan’s public administration arena​​. Importantly, the study attempts to find a way for Korea to strengthen the public administration arena in ​​Azerbaijan through aid projects, and thereby contribute to the county’s national development. As a result of applying text mining analysis and decision tree analysis, it can be seen that policy issues such as tourism and agriculture, the introduction of a new economic system and business attraction are important. In addition, the study suggests that strengthening Azerbaijan’s ability to control corruption is important from the Korean point of view.